Collected liturgical writings of Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje on the Bkaʼ ma Na rag doṅ sprugs, the Gter kah Goṅ ʼOg, and other revelations of the past, presented according to the liturgical practices of Smin-grol-gliṅ Monastery - Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje, 1646-1714 (D. G. Khochhen Tulku, 1977)
Rituals of the Nyingmapa tradition.